Communication Strategy Of The Merah Putih Cooperative Policy In Improving Community Welfare - Bonardo Marulitua A; Ade Risna Sari; Bambang Amir Alhakim; Gregorius Cristison Bertholomeus; Ita Erliyani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Merah Putih Cooperative is a strategic policy instrument based on a people's economy designed to strengthen financial independence and improve community welfare at the local level. However, the effectiveness of this public policy implementation depends heavily on how program messages are disseminated and understood by the target community. This study aims to analyze and describe the communication strategy of the Merah Putih Cooperative policy in improving community welfare, as well as to identify supporting and inhibiting factors in the message transmission process. This study uses a qualitative approach with a descriptive case study method. Data collection was conducted through in-depth interviews with cooperative administrators, local government officials, and community members, as well as participant observation and policy documentation. Data analysis was carried out using data condensation techniques, data presentation, and drawing conclusions based on the theoretical framework of public policy communication strategy analysis. The results of the study indicate that the communication strategy implemented includes a combination of mass communication media and a local wisdom approach (dialogic-participatory). Face-to-face socialization through community forums proved to be the most effective channel in building trust and credibility of the institution. However, communication barriers in the form of technical-operational barriers and varying levels of community financial literacy remain major challenges. This study concludes that adaptive, community-based policy communication strategies can increase active citizen participation, ultimately positively impacting the economic and social well-being of communities. The implications of this research emphasize the importance of sustainable integration of digital and conventional communication channels for regional economic policymakers